Transformacja na rynku mieszkaniowym w Polsce – następstwa i perspektywa na przyszłość - Kucharski, Krzysztof (PRAWO i WIĘŹ, 2025)
The fundamental assumption of a market economy is that it aims to balance supply and demand. Achieving equilibrium is an optimisation goal for the economy. However, the situation in the housing market under domestic conditions is a prime example of a quantitative supply-demand crisis. This warrants a review and re-evaluation of the current market mechanisms. For, in accordance with the adopted economic model, the state is obliged to correct market mechanisms (Article 20 of the Constitution of the Republic of Poland) and to take due care in terms of satisfaction of housing needs (Article 75 of the Constitution of the Republic of Poland). After all, the situation on the housing market influences the standing of the entire economy and has a significant effect on social affairs.